No evidence for self-recognition in a small passerine, the great tit (Parus major) judged from the mark/mirror test - Kraft, Fanny-Linn; Forštová, Tereza; Utku Urhan, A; Exnerová, Alice; Brodin, Anders (Animal cognition, 2017)
Self-recognition is a trait presumed to be associated with high levels of cognition and something previously considered to be exclusive to humans and possibly apes. The most common test of self-recognition is the mark/mirror test of whether an animal can understand that it sees its own reflection in a mirror. The usual design is that an animal is marked with a colour spot somewhere on the body where the spot can only be seen by the animal by using a mirror. Very few species have passed this test, and among birds, only magpies have been affirmatively demonstrated to pass it. In this study, we tested great tits (Parus major), small passerines, that are known for their innovative foraging skills and good problem-solving abilities, in the mirror self-recognition test. We found no indication that they have any ability of this kind and believe that they are unlikely to be capable of this type of self-recognition.
Keywords: Recognition, Psychology; Animals; Female; rozpoznávání (psychologie); Great tit; ženské pohlaví; Parus major; Passeriformes; chování zvířat; Visual Perception; Mirror test; kognice; zraková percepce; Male; Cognition; Behavior, Animal; Colour mark; Self-recognition; mužské pohlaví; zvířata